Evaluasi penyelenggaraan praktikum isolasi DNA dengan metode kolom di Laboratorium Biokimia dan Gizi Fakultas Kedokteran Universitas Islam Indonesia - Mujiyanto Mujiyanto (Poltekkes Kemenkes Yogyakarta, 2025)
DNA isolation is a fundamental technique in molecular biology and medical research. Despite its importance, structured evaluations of DNA isolation practicums in medical education remain limited, particularly in Indonesia. This study aimed to evaluate the effectiveness of a column-based DNA isolation practicum in improving students’ understanding of biomolecular techniques. A quasi-experimental pretest–posttest design was conducted with 163 second-year medical students at Universitas Islam Indonesia. Whole blood samples were used for DNA isolation employing a commercial column-based kit (Favorgen). DNA concentration was measured using a NanoDrop spectrophotometer (ng/µL). Students’ knowledge was assessed through pretest and posttest scores, and learning experiences were further evaluated using a structured questionnaire on teaching assistant performance and laboratory facilities. Data were analyzed using paired t-tests and descriptive statistics (SPSS v23). The practicum yielded DNA concentrations ranging from 26.25 to 1495.73 ng/µL, although one sample failed to be detected. Students’ mean test scores significantly increased from 64.63 (SD 24.28) to 93.19 (SD 11.32) (p < 0.001). Questionnaire results demonstrated high satisfaction, with mean ratings of 3.94 for assistant performance and 3.93 for laboratory facilities (scale 0–4). The column-based DNA isolation practicum effectively enhanced students’ theoretical knowledge and provided hands-on experience in molecular laboratory skills. Despite some variability in DNA yield, the overall evaluation indicates strong pedagogical value. These findings support the integration of structured DNA isolation practicums into medical curricula to strengthen competency in biomolecular sciences. Future research should explore long-term retention of skills and optimization of practical protocols.